Coaching sprinting: Expert coaches` perception of resistance-based training - Bolger, R.; Lyons, M.; Harrison, A. J.; Kenny, I. C. (International Journal of Sports Science & Coaching, 2016)
The aim of this study was to explore expert coaches` perceptions of resistance-based training for sprinting. This research posed three broad questions: (i) What resistance exercises are being performed by competitive sprinters? (ii) Why coaches have selected these exercises over others? (iii) How athletics coaches control and implement their use in training? Participants for the study comprised seven expert track and field sprint coaches. Findings indicated that the coaches used a variety of resistance-based training including variations of the squat, Olympic weightlifting movements and deadlift, along with resisted running in the form of weighted jackets, hill running, and weighted sleds. They also used plyometric variations of bounding and specific drills. Particular emphasis was drawn towards variations of the squat and how exercises transferred from the weights room to the track. All coaches changed exercises to complement the focus from off-season to in-season. The main finding of this study relates to the current dearth of research to support evidence-based resistance exercise prescription for sprinters. ABSTRACT FROM AUTHOR